Effect of Scan Rate and pH on Determination Amoxilline Using Screen Printed Carbon Electrode Modified With Functionalized Graphene Oxide - Latif, Issam A.; Merza, Sundus H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Graphene oxide GO was functionalized with 4-amino, 3-substituted 1H, 1, 2, 4 Triazole 5(4H) thion (ASTT) to obtain GOT. GOT characterized by FT-IR, XRD.via modification of the working electrode of the SPCE with the prepared nanomaterial ( GOT) the effect of scan rate and pH on the determination of Amoxilline (AMOX) was studied using cyclic voltammetry. AMOX show various responses at pH ranging from 2 to 7 and also was observed sharp increase in the oxidation peaks in the pH 3. The formal potential (midpoint) for AMOX was highly pH-dependent. From the effect of scan rate, surface coverage concentration of electroactive species the values of the electron transfer coefficient and the electron transfer constant rate ket was obtained as 5.39Ã—10-10 molcm-2, 0.5, and 2.45Ã—10-3 cm.s-1respectively.